Диференціація кінематики греблі Дністровської ГЕС-1 (за даними ГНСС-моніторингу просторових зміщень) - Третяк, К.; Корлятович, Т.; Брусак, І.; Смірнова, О.; Tretyak, K.; Korliatovych, T.; Brusak, I.; Smirnova, O. (Видавництво Львівської політехніки, 2021)
Мета цієї роботи – узагальнення висотних зміщень ГНСС-мережі просторового моніторингу греблі Дністровської ГЕС-1 для диференціації її кінематики та оцінювання впливу короткотривалих геодинамічних процесів на цій території. Об’єкт дослідження. Об’єктом дослідження є моніторинг греблі Дністровської ГЕС-1 за даними ГНСС-мережі стаціонарної системи моніторингу просторових зміщень споруд (ССМПЗС) Дністровської ГЕС-1. Основою Дністровської ССМПЗС є дві базові ГНСС-станції, додатково оснащені роботизованим тахеометром, які встановлені на потужному фундаменті та розміщені на відстані кілька сотень метрів від греблі. На гребені греблі розміщені контрольні пункти, оснащені ГНСС-приймачем з антеною і кутниковим відбивачем із 3600 кутом огляду. Результати ГНСС-вимірювань передаються у програмне забезпечення Leica GNSS Spider, у якому здійснюється опрацювання та визначення координат базових та контрольних пунктів. У програмному забезпеченні GEOMOS виконується спільне урівноваження результатів ГНСС та лінійно-кутових вимірювань. Методика. Для узагальнення зміщень ГНСС-станцій Дністровської ГЕС-1 використано метод статистичного аналізу часових серій. Виконано пошук коваріаційних взаємозв’язків між усіма ГНСС-станціями ССМПЗС Дністровської ГЕС-1, що розміщені на греблі, за результатами вимірювань з 1.07.2017 р. до 31.03.2021 р. Для виділених періодів аномальних короткотривалих зміщень обчислено середні значення коваріації для кожної ГНСС-станції. Результати. За період з 1.07.2017 р. до 31.03.2021 р. за результатами коваріаційних зв’язків для більшості ГНСС-станцій виявлено три епохи аномальних висотних зміщень (Т = 2017.8 ±0.1, Т= 2019.0 ±0.1, Т = 2019.4 ±0.1). На основі коваріаційного аналізу встановлено, що в періоди аномальних вертикальних зміщень кінематика ГНСС-станції МР01 істотно відрізняється від кінематики ГНСС-станцій МР02-МР05. Кінематика ГНСС-станцій МР02-МР05 є сталою, що свідчить про аномальність руху блока, на якому встановлена ГНСС-станція МР01, щодо решти блоків греблі Дністровської ГЕС-1. Наукова новизна та практична значущість. Запропоновано метод для вивчення геодинаміки великих промислових територій, покритих мережею ГНСС-станцій. За результатами ГНСС-вимірювань виявлено періоди аномальних зміщень та виконано пошук просторових кінематичних взаємозв’язків між окремими ГНСС-станціями. Розроблену методику можна використовувати для диференціації кінематики конструктивних елементів інженерних споруд, промислових територій, геодинамічних полігонів, на території яких встановлені ГНСС-станції.

The purpose of study is to generalize the vertical displacements of the GNSS network of spatial monitoring of the Dnister HPP-1 dam for the differentiation of its kinematics as well as to evaluate the impact of short-term geodynamic processes in the region. Object of study. The object of the study is the monitoring of the Dniester HPP-1 dam according to the GNSS network data of the stationary system for monitoring the spatial displacement of structures (SSMSDS) of the Dniester HPP-1. The basis of the Dnister SSMSDS are two base GNSS stations additionally equipped with a robotic total station, which are installed on a strong foundation and located at a distance of several hundred meters from the dam. There are control points equipped with a GNSS receiver, antenna and an angle reflector with a 3600 viewing angle on the crest of the dam. The results of GNSS measurements are transmitted to the Leica GNSS Spider software, which processes and determines the coordinates of the base and control points. The GEOMOS software performs a joint estimation of GNSS results and linear-angular measurements. Methodology. To generalize the displacements of GNSS stations of Dnister HPP-1 the method of statistical analysis of time series is used. Authors examine the covariance interrelationships between all GNSS stations of the stationary system for monitoring the spatial displacement of structures (SSMSDS) of the Dnister HPP-1, which are placed on the dam based on the results of measurements from 1.07.2017 to 31.03.2021. For the selected periods of anomalous short-term displacements, the average values of covariance for each GNSS station are calculated. Results. During the period from 1.07.2017 to 31.03.2021 and according to the results of covariance interrelation for most GNSS stations, 3 epochs of anomalous altitude displacements are established (T = 2017.8 ± 0.1, T = 2019.0 ± 0.1, T = 2019.4 ± 0.1). Based on the covariance analysis, it was found that for periods of anomalous vertical displacements, the kinematics of the GNSS station MP01 differs significantly from the kinematics of GNSS stations MP02-MP05. The kinematics of GNSS-stations MP02-MP05 is constant, which indicates the anomalous movement of the unit on which the GNSS-station MP01 is installed in relation to the other blocks of the dam of the Dnister HPP-1. Scientific novelty and practical significance. Authors proposed the method for studying the geodynamics possesses of large industrial areas covered by a network of GNSS stations. Based on the GNSS measurements the periods of anomalous displacement are reveled and further search for spatial kinematic interrelationships between pair of GNSS stations is established. The developed methodology can be used to differentiate the kinematics of structural elements with installed GNSS stations such as engineering structures, industrial areas, geodynamic polygons.
Differentiation of kinematics of the Dnister HPP-1 dam (based on the data of GNSS monitoring of spatial displacements)
Keywords: ГНСС-вимірювання; моніторинг; Дністровська ГЕС-1; ГНСС-мережа; просторові зміщення; GNSS measurements; monitoring; Dnister HPP-1; GNSS network; spatial displacements; 528.21